Smallholder reforestation and livelihoods in the humid tropics: a systematic mapping study - Ota, Liz; Herbohn, John; Harrison, Steve; Gregorio, Nestor; Engel, Vera Lex [UNESP] (Springer Nature, 2017)
Systematic mapping studies provide a snapshot of the literature based on systematic literature searches. In this systematic mapping study, the original research that links reforestation and livelihoods in the tropics was mapped and analysed to identify the trends, biases and gaps in the literature. In total, 339 papers from 92 journals were identified. Agroforestry Systems was the journal in which articles were most frequently published, and Cameroon and Indonesia the most frequently studied countries. The greatest number of authors came from the USA, and authors were most commonly affiliated with ICRAF. A limited collaboration between research groups in the tropical regions was identified. Anthropology and Social Sciences were the most frequent areas of research, especially in Africa. Latin America had more technical studies and more publications discussing payment for environmental services than the other regions. Based on the temporal analysis of the main terms in abstracts of the publications included, it was found that agriculture-related terms and terms related to the human component in the landscape were consistently prevalent in the literature relating reforestation and livelihoods throughout time. Agroforestry systems were especially important in small-scale reforestation and livelihoods. Trends, biases and gaps were discussed. Broader cooperation between tropical regions and between clusters of authors would be beneficial for research and practice.
Keywords: Agroforestry; Community forestry; Forest restoration; Systematic map; Systematic search